1993
DOI: 10.1111/j.1471-4159.1993.tb07480.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Human Amylin in Rat Primary Hippocampal Cultures: Similarity to Alzheimer's Disease Amyloid‐β Neurotoxicity

Abstract: Amylin, a 37-amino-acid amyloidogenic peptide, bears biophysical similarities to the amyloid-beta peptide (A beta) deposited in Alzheimer's disease. Using embryonic rat hippocampal cultures we tested whether amylin induces neurotoxicity similar to that previously observed with A beta(1-40). Treatment with human amylin(1-37) resulted in prominent toxicity as assessed by phase-contrast microscopy and quantification of lactate dehydrogenase in the medium. Amylin-induced neurotoxicity was morphologically similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 24 publications
(39 reference statements)
9
103
0
Order By: Relevance
“…This is consistent with an earlier paper suggesting that full-length human amylin resulted in prominent toxicity in rat primary HN cells [24]. Also, it has been shown that, in contrast to full-length amylin, which promotes self-assembly and aggregation, various amylin peptide fragments (including amino acid residues 20-29) were non-toxic at similar concentrations in rat primary hippocampal cultures, suggesting that secondary structure may play a predominant role in human amylin neurotoxicity [24]. Hence, further work needs to be done using various amylin peptide fragments not only in hippocampal cells but also in hypothalamic cells.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is consistent with an earlier paper suggesting that full-length human amylin resulted in prominent toxicity in rat primary HN cells [24]. Also, it has been shown that, in contrast to full-length amylin, which promotes self-assembly and aggregation, various amylin peptide fragments (including amino acid residues 20-29) were non-toxic at similar concentrations in rat primary hippocampal cultures, suggesting that secondary structure may play a predominant role in human amylin neurotoxicity [24]. Hence, further work needs to be done using various amylin peptide fragments not only in hippocampal cells but also in hypothalamic cells.…”
Section: Discussionsupporting
confidence: 82%
“…It has also been proposed that high levels of leptin are associated with lower rates of dementia and Alzheimer's disease [31]. Amylin acts at the level of the CNS to produce anorectic effects, alter physiological responses to feeding (and possibly thirst and drinking behaviour) [23] and drive the neurite degeneration in Alzheimer's disease [24]. Adiponectin has been proposed to exert multiple regulatory functions primarily through action on the CNS [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other amyloidogenic proteins, which do not share sequence homology with A␤ (e.g.. prion and amylin), do form structurally similar extracellular deposits and have been found to have similar neurotoxic activity in vitro (47,48). One possible mechanism that could explain the common biological activity seen with different amyloidogenic peptides is ␤-sheet augmentation, whereby a peptide forms a "peptide-surface association" (49) either by inserting itself into a ␤-sheet-containing domain (50), which has been proposed for other diseases involving protein conformational changes (51)(52)(53)(54), or by adding to the edge of an anti-parallel ␤-strand, as has been implicated in regulating protein associations governing signal transduction pathways and assembly interactions in certain viral capsids (49).…”
Section: Discussionmentioning
confidence: 99%